The reflection of history through José María Merino (XXI Century. Spanish Literature and Culture, 2017)
One of the facets that define part of the narrative work of José María Merino (La Coruña, 1941) is the appearance of historical elements as backbone of the argument. Sometimes these elements are exposed briefly, however, in others, they are the central element of the story, being able to classify said works under the label of "historical novels". In this work we intend to delve into some of these titles - Las visiones de Lucrecia (1996), El heredero (2003), La sima (2009), Musa Décima (2016) - to appreciate the differences in the disposition that the author makes of History and the role that it has as a narrative element.